Implementación de un café-restaurant, y su impacto en la economía en el cantón Buena Fe, año 2022 - Moreira Pérez, Lady Valeria (2022)
The purpose of this project is the implementation of a cafeteria-restaurant that is part of the new national and global tourism trends such as sustainable tourism and gastronomic tourism. We have structured this document in three parts: the first contains the theoretical foundations that support the research. The second part contains the techniques applied to collect the information. And the third contains the results obtained. The techniques applied for data collection is the core of the project because it contains the description of the proposed tourism project: Sustainable Coffe- restaurant located in the facilities of the Buena Fe service Staion.This place has been chosen for the location of the coffe-restaurant, considering that is a place that is positioned for tourism, that has natural and comfortable elements that reinforce the concept of the restaurant. It is concluded that the degree of acceptance is 78%, which shows that the implementation of a caffe- restaurant in the sector, is necessary. Regarding the financial analysis carried out on a caffe in the sector, the financial indicators are a NPV of $23.000, IRR of 45%, and a PRI of 1 year 4 months, likewise the Benefit-Cost Ratio (BC) is 1.83, which indicates that the implementation of a caffe-restaurant is a feasible and wil contribute to the socioeconomic development of the sector.